Implementation of training programs and their impact on employee competency at PT BRI Persero in Probolinggo - Lukmanul Hakim; Elok Sulusiah; Fais Abdul Hadi; Ainur Rofiqi; Yeni Kartikawati (Economic: Journal Economic and Business, 2026)
Human resource development through training is a strategic investment to strengthen the competitiveness of banking companies. PT Bank Rakyat Indonesia (Persero) Tbk in Probolinggo implements various training programs to improve employee capabilities in responding to the increasingly competitive developments in the banking industry. The successful implementation of training programs is a crucial factor in achieving optimal employee competency improvement, thus requiring a comprehensive evaluation of the implementation process and the results obtained. This study aims to analyze the implementation of training programs conducted by PT Bank Rakyat Indonesia (Persero) Tbk in Probolinggo and evaluate the impact of these training programs on employee competency. This study uses a quantitative approach with descriptive methods to obtain a comprehensive picture of the phenomena that are the focus of the study. Data collection was conducted through review and analysis of various relevant written sources. The results show that the implementation of training programs at PT Bank Rakyat Indonesia (Persero) Tbk Probolinggo is carried out in a structured manner through several stages, namely identifying training needs, planning, implementation, and evaluation. The training program includes improving technical competency in the banking sector, developing managerial capabilities, and strengthening soft skills tailored to individual and organizational needs.